The Emergence of Humans and the Origin of Vietnamese Ethnic Groups from Vietnamese Myths - Nguyen Thi Tu Trinh (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
The origin of humans has been at the center of attention throughout most of the history of humanity and remained debatable. Humankind is more interested in tracing back his ancestors than ever. The theory of evolution by natural selection, first formulated in Darwin’s book “On the Origin of Species” in 1859, shows that most species are descended from common ancestors. However, most countries and ethnic groups have their own explanation and interpretation of the origin of humans from the dawn of the civilization in their myths. Particularly, many myths and legends about the beginnings of humans have cropped up and varied across religions, races, ethnics, nations and reflect their daily and spiritual life as well as their beliefs. This paper is devoted to exploring 24 Vietnamese myths concerning the emergence of humans and Vietnamese ethnic groups from the earliest time within a motif-based approach. The study reveals that most collected Vietnamese myths of human emergence are utterly imaginative, artistic and creative with a wide variety of motifs. They bear, however, some similarities in the plot and motif such as: (i) creation of Vietnamese people from eggs, gourds and clay; (ii) natural disasters like floods and droughts and (iii) consanguineous marriage and animal marriage. Last but not least, mythical narration and epic poems play a crucial role in Vietnamese literature, history, religions, beliefs and culture. The author does not aim at comparing origin myths of Vietnam and other countries in this paper but generally introduce the reader to these myths. Received 18th September 2019; Revised 19th February 2020; Accepted 20th March 2020